2011
DOI: 10.1673/031.011.17101
|View full text |Cite
|
Sign up to set email alerts
|

Raft Formation by the Red Imported Fire Ant,Solenopsis invicta

Abstract: The raft behavior of the invasive red imported fire ant, Solenopsis invicta Buren (Hymenoptera: Formicidae), has been documented for over a century. However, no rigorous tests have been performed elucidating the structure, limits, and important characteristics of this behavior. Rafting makes S. invicta competitive in both native and foreign environments. Further understanding of this behavior will provide critical advancement to the comprehension of this ant's global invasion ecology.Though speculations exist,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 19 publications
(55 reference statements)
1
47
1
Order By: Relevance
“…In the simplest case, entire colonies form rafts of workers and brood on the water surface. This behavior was described in detail for Solenopsis (Adams et al, 2011;Mlot et al, 2011), but also occurs in some Wasmannia and Pheidole species (Robson, 2010; S.P.Y., personal observation). Other rainforest taxa, such as Ectatomma ruidum in Central America, will voluntarily walk beneath the surface of puddles on the forest floor (S.P.Y., personal observation), and workers of Camponotus schmitzi forage for insect prey by crawling or swimming into the water held by Nepenthes pitchers in Asia (Bohn et al, 2012).…”
Section: Research Articlementioning
confidence: 71%
“…In the simplest case, entire colonies form rafts of workers and brood on the water surface. This behavior was described in detail for Solenopsis (Adams et al, 2011;Mlot et al, 2011), but also occurs in some Wasmannia and Pheidole species (Robson, 2010; S.P.Y., personal observation). Other rainforest taxa, such as Ectatomma ruidum in Central America, will voluntarily walk beneath the surface of puddles on the forest floor (S.P.Y., personal observation), and workers of Camponotus schmitzi forage for insect prey by crawling or swimming into the water held by Nepenthes pitchers in Asia (Bohn et al, 2012).…”
Section: Research Articlementioning
confidence: 71%
“…() reported that the exoskeleton of individual S. invicta is moderately hydrophobic, which can enhance water repellency on the water surface and favor floating. In addition, S. invicta individuals link their bodies together using a combination of mandibles and tarsi (Adams et al ., ; Mlot et al ., ). Likewise, utilization of hydrophobicity (climbing, walking and flowing on the sucrose droplet) and body connection by S. invicta workers is important for stacking and covering processes observed in the present study (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Biphasic secretion True bugs, [469,470] tenebrionid beetles, [638] fire ants [639] Built structures Green lacewings [640] Froths and foams Pyrgomorphid grasshoppers, [641] lubber grasshoppers, [642] froghopper nymphs [474] Hemolymph defense Sawflies, [643,644] katydids, [450,645] stoneflies, [645] stonefly nymphs [646] Projectile dispersal Stick insects, [451,459] termites [647] Material motif General functionality System of interest Insect and reference Thermoregulation Cooling Honeybees, [410] mosquitos, [411] sawflies [412] Water active properties Surface excretion Leafhoppers [166,167,648] Layering Collective materials Built structures Social wasps [649,650] Raft building to survive flooding Fire ants [580] Bivouac assemblies Army ants [512] Color vision and color manipulation Impedance matching Dragonflies, [337] cicadas, [339] butterflies, [338,341,342] moths, [342,343] beetles [342] Water active properties Desiccation resistance Antarctic midges, [651] African lake flies [652] Regular repeated patterns…”
Section: Physical Adhesive Systemsmentioning
confidence: 99%
“…[572,579] Fire ants native to the rainforests of Brazil, Solenopsis invicta, are known for forming floating rafts in response to habitat flooding ( Figure 25B); they are able to survive floating on these rafts for up to 12 consecutive days. [580] While an individual ant has a somewhat hydrophobic integument (contact angle θ e = 102°) and is denser than water, ant aggregations become over five times less dense and significantly more water-repellent (θ e = 133°) in accordance with the Cassie-Baxter law as their newfound collective buoyancy decreases their area fraction of water contact. [581] Recent years have seen a number of studies that obtain quantitative measures of the remarkable properties of ant aggregations, which can be compared with other types of "entangled active matter" such as cells, which also have actively regulated physical bonds.…”
Section: Insect Swarms As Functional Materialsmentioning
confidence: 99%